Characteristics of the environmental matrix in the Romanian Black Sea area - Carmen Gasparotti (Annals of "Dunărea de Jos" University of Galaţi: Fascicle XI Shipbuilding, 2015)
The paper aims to present the main features of the environmental matrix in the Black Sea, whose trends and variability are extremely important issues for a wide range of marine activities. Therefore, the knowledge of wave and wind climate is vital for coastal infrastructure, including ports design, erosion and shoreline protection, sediment transport, etc. The paper summarizes the observations obtained from the meteorological stations Sulina, Constanta and Mangalia, as well as the satellite data regarding the wind regime, taking into account their frequency and speed on the cardinal points direction, and the frequency, intensity and duration of the storms. The study shows that winds regime is characterized by a wide variability both in direction and speed, and the storms on the Romanian coast of the Black Sea occur especially in the cold season. The paper also presents data regarding the waves regime considering the direction of the waves, their height and period. The waves along the Romanian Black Sea coast are produced mainly by the wind, whereas the swell rarely appears.. As a result, the regime of the waves is influenced by the winds. The dominant waves direction from the distance is north up to the east.